(untitled) (Sustainable Construction (SUSCON), 2025)
The economic activities surrounding Inobonto Market play a significant role in increasing vehicle mobility along the Trans-Sulawesi Highway. However, this growth has been accompanied by serious transportation issues, particularly road surface deterioration and reduced traffic capacity. Damaged pavements—characterized by potholes, cracks, and uneven surfaces—cause drivers to reduce speed or change lanes suddenly, disrupting traffic flow stability. At the same time, trading activities such as on-street parking, loading and unloading of goods, and the dense movement of pedestrians create additional side friction that narrows the effective road width. The combination of these factors leads to a decline in the road’s service level and hampers the smooth distribution of goods in the market area. This study aims to analyze how pavement damage and local economic activity simultaneously affect the operational capacity of roads around Inobonto Market. The findings are expected to provide a scientific basis for local governments in formulating strategies for road maintenance and market activity management, ensuring a sustainable balance between transportation efficiency and economic development.